O bibliotecário como mediador da informação: o desafio de resgatar o gosto pela leitura no grupo da terceira idade SESI / Ananindeua / PA - MONTEIRO, Héliton José da Silva (2021)
The approach work is the absence of activities and practices that exercise the intellectual side and not only the body of the elderly of the SESI senior group, with the purpose of preventing common dementias in the elderly. Faced with this problem, it was aimed to awaken the taste for reading in the elderly of the elderly group of SESI, as prevention to mental sedentarism and dementias / Alzheimer. This research work was based on a descriptive / practical methodology and will make use of two "quali-quanti" methods. Data were collected through questionnaires with closed questions applied to a sample of the universe of the elderly of the group. From this context the research aims to draw the attention of projects, coordinators and groups belonging to the elderly, to the evils such as dementias arising from not exercising the mind in the elderly, as well as the benefits of having an active and dynamic mind for a healthy aging.